Saṃvat 1981 sāla, Mārga 14 gate Śukravārakā dina, Śrī 3 Mahārāja Candrasamśera Jaṅga Bahādura Rāṇā, Ji. Si. Bi., Ji. Si. Es. Āī., Ji. Si. Em. Ji., Ji. Si. Bhi. O., Ḍi. Si. Ela., Thoṅa-Liṅa-Pimmā-Ko-Kāṅa-Vāṅa-Syāna, Prāimminishṭara āṇḍa Mārśala, bāṭa bhāradāra, aphisara, ra bhalādamīharū jambāgarī kariyāko amalekha garne bāremā vicāra garnālāī Ṭunḍikhelamā bakseko spīca - Candra Shum Shere, Maharaja of Nepal, fl. 1901-1929 (Su. Rāmamaṇī Ā. Dī., 1924)
Lecture delivered by the prime minister of Nepal on the theme of public support for the emancipation of slaves.